A reappraisal of the surgical planning of the superficial circumflex iliac artery perforator flap. Issue 4 (April 2017) - Feng, Shaoqing; Xi, Wenjing; Zhang, Zheng; Tremp, Mathias; Schaefer, Dirk J.; Sadigh, Parviz L.; Zhang, Wenjie; Zhang, Yi Xin
Summary: Objective: The popularity of the superficial circumflex iliac artery perforator (SCIP) flap has been limited by factors such as variable vascular anatomy and short arterial pedicle. This article aimed to delineate flap design and harvest strategies based around either the proximal or distal perforators of the superficial circumflex iliac artery (SCIA) and propose a set of strategies that can help deal with the limitations of the flap. Method: From August 2011 to June 2015, the SCIP flap was used in 80 patients for soft tissue defects at our institution. We utilized vessel imaging navigation to get a detailed overview of the vascular anatomy preoperatively. Flaps were designed on the basis of either the proximal or distal perforators of the SCIA. Backup strategies and surgical maneuvers were suggested to solve the problems that emerged during surgery. Results: In total, 51 flaps were raised on the basis of the proximal perforators of the superficial branch of the SCIA, whereas 25 cases were based on the distal perforators from the deep branch, and in four cases, the pedicle was switched to the superficial inferior epigastric artery. In eight cases, the arterial pedicle lengthen technique was applied with a maximum length of 10 cm. All donor sites were closed directly with inconspicuous scars. Conclusion: These surgical strategies simplified the intraoperative decision-making and overcame the shortcomings of the SCIP flap. We believe that the SCIP flap has a great potential to become a new workhorse flap in the field of reconstructive surgery.